Assessing the Key Construction Safety Challenges in Sri Lanka: A Survey-Based Study - Asela Weerakoon; David Thorpe; Amirhossein Heravi; Subrata Chakraborty (Safety)
The construction industry is a key driver of economic development in a developing country like Sri Lanka. However, many construction projects still face serious safety challenge areas such as poor attitude, bad conduct, negligence, out-of-date legislation, a lack of qualified safety officers and financial constraints. This study aims to determine which safety challenges are the key ones in the Sri Lankan construction industry and how these challenges are classified and related to each other. The significance of this research is that it identifies the most important safety challenge areas and addresses them, which helps to overcome other safety challenge areas that rely on them. To achieve this aim, survey questionnaires were developed, and a survey was conducted among key project stakeholders, including safety officers, engineers, managers, quantity surveyors and human resources personnel, to collect information on significant safety factors that can help in improving safety. Forty-three safety challenge elements were identified and assessed through factor analysis. The ten most significant safety challenge elements were extracted and categorised into two main categories: (i) economy-related and (ii) human-resource-related challenges. The results of this survey provide a very good foundation for project managers or safety managers to identify certain criteria when selecting construction staff and making project plans.